Medição de múltiplas fases de nível de líquidos usando filtro adaptativo: técnicas, métodos e simulações - Oliveira, José Igor Santos de (2005)
The level measurement, besides the applications in reservoirs of industrial processes, as in the industries chemical, pharmaceutical, chemical petroleum, of I refine of alumina etc, it is applicable also in reservoirs exposed outdoors, such as dikes, lakes and ponds, dams and other. To measure level in most of the cases has great impact in the people's safety, of the environment, and of the involved process, besides influencing in the quality of the final product. Level in several ways can be measured that space from a simple float to a sophisticated system for time of flight of waves that processes the information that returns after the emission of a sign. System as that can use several types of waves to take the information of the transmission, the most common are microwaves, infrared and the ultrasonic ones. In that work a method is described that is used of the technique of the time of flight with the use of ultrasonic waves in association with the adaptive filtering to determine the location of the levels of the liquids contained in a container of known height. It is made a study of robustness of the method with base in simulations, through the variation of the relationship sign noise and of the sampling tax, in comparison with the results obtained with the use of Hilbert Transform, Fourier Transform and Wavelet Transform, considering the time of processing and the measurement uncertainty.